2020
DOI: 10.1097/pcc.0000000000002202
|View full text |Cite
|
Sign up to set email alerts
|

Stress Ulcer Prophylaxis in Critically Ill Children: A Multicenter Observational Study

Abstract: Objective: To describe current stress ulcer prophylaxis practice in Canadian PICUs. Design: Multicenter cohort study. We defined stress ulcer prophylaxis as the use of a proton-pump inhibitor, histamine-2 receptor antagonist, or sucralfate within the first 2 PICU days among children who had not been on these medications at home and had no evidence of gastrointestinal bleeding. Setting: Seven PICUs in Canada.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This rate is significantly higher than rates reported in observational studies. A recent study assessed current practice and bleeding rates in Canadian PICUs and observed that GI bleeding occurred in 6% of the children and clinically important GI bleeding in 0.8% 46 . This discrepancy could potentially reflect improvements in intensive care in recent decades (>50% of trials included are more than 20 years old), the large heterogeneity in trial quality, trial populations and definitions of GI bleeding in the included trials of this systematic review.…”
Section: Discussionmentioning
confidence: 96%
“…This rate is significantly higher than rates reported in observational studies. A recent study assessed current practice and bleeding rates in Canadian PICUs and observed that GI bleeding occurred in 6% of the children and clinically important GI bleeding in 0.8% 46 . This discrepancy could potentially reflect improvements in intensive care in recent decades (>50% of trials included are more than 20 years old), the large heterogeneity in trial quality, trial populations and definitions of GI bleeding in the included trials of this systematic review.…”
Section: Discussionmentioning
confidence: 96%
“…We speculate that eSIMPLER’s clear display of CDS for indications, current EHR orders (or lack thereof), and a prompt to indicate whether the team believed SUP was indicated each day led to a “pause” and team discussion whether to initiate, continue, or discontinue SUP and ultimately reduced discrepancies between SUP indications, team intent, and SUP prescribing. Although we did not specifically evaluate whether SUP use was clinically indicated, prior studies have shown high rates of SUP use in the PICU, but low incidence of clinically significant gastrointestinal bleeding (19, 20). We also showed that VTE prophylaxis prescribing increased in proportion to increased need for VTE prophylaxis recorded in eSIMPLER.…”
Section: Discussionmentioning
confidence: 99%
“…Medications, including histamine-2-receptor antagonists (H2RA) and proton pump inhibitors (PPIs), are often used to protect the gastrointestinal tract from mucosal damage during critical illness [57 ▪▪ ] and reduce the risk of gastrointestinal bleeding that may occur due to stress-related ulceration [58]. A large multicenter observational study in Canadian PICUs and a separate international, observational study both reported that ∼70% of patients received stress ulcer prophylaxis (SUP) [1 ▪▪ ,57 ▪▪ ]. In the Canadian study, the distribution of SUP use was 66% for H2RA and 47% for PPIs and patients who received SUP were older, received less enteral nutrition and received more corticosteroids or nonsteroidal anti-inflammatory drugs [57 ▪▪ ].…”
Section: Enteral Nutritionmentioning
confidence: 99%